Pelatihan dan Pendampingan Penerapan Komposter Sebagai Pengolahan Sampah Organik Rumah Tangga Menjadi Kompos - Joleha Joleha; Elvi Yenie; Bochari Bochari; Imam Suprayogi; Feranita Feranita (Journal of Community Engagement Research for Sustainability, 2022)
This training and mentoring for the application of the composter is part of an integrated community service activity with Kukerta students at the University of Riau in 2021. This activity was carried out in RT/RW 03/09 Sidomulyo Barat Village, Tuahmadani District, Pekanbaru City. The purpose of this activity is to implement Komposter as processing organic waste into compost, reducing waste production and environmental pollution. The participants of this activity were mothers from housing residents as many as 65 people. The method used in this activity includes an understanding of making composter and compost from household waste. The series of activities consist of 1) exposure to composting; 2) Composting practices and how to use a composter, 3) Monitoring the composting temperature, pH and humidity. Through this training and mentoring activity, participants gain knowledge and experience in making composters to produce compost. Participants also feel that this activity can reduce waste, air pollution due to the smell of organic waste by using it as compost which is useful for growing vegetables or ornamental plants and can also reduce waste generation in Final Disposal Sites (TPA).